Embelin Induces Apoptosis in Human Glioma Cells Through Inactivating NF-κB - Sang-Yoon Park; Sung-Lyul Lim; Hyeung-Jin Jang; Jun-Hee Lee; Jae-Young Um; Sung-Hoon Kim; Kwang Seok Ahn; Seok-Geun Lee (Elsevier, 2013)
Aggressive tumor growth and diffuse tissue invasion are hallmarks of malignant glioma. Embelin is an active compound identified as a novel XIAP inhibitor from the Embelia ribes that exhibits various medicinal effects including anti-inflammatory and anti-cancer activities. In the present study, we investigated whether embelin could have a therapeutic effect in glioma. We found that embelin suppressed proliferation of human glioma cells, but not in normal immortalized human astrocytes. In addition, embelin induced apoptosis in human glioma cells by inhibiting NF-κB, which is a crucial transcription factor associated with several human diseases including cancer and controls multiple genes involved in tumor progression such as cell proliferation and survival. Intriguingly, embelin had no inhibitory effect on XIAP in glioma cells even though discovered as an XIAP inhibitor, but instead inhibited NF-κB activity by reducing nuclear translocation of p65 through decreasing phosphorylation and proteasomal degradation of IκBα in glioma cells. Furthermore, p65 overexpression decreased embelin-induced apoptosis in glioma cells. Taken together these results indicate that embelin could be a potent novel therapeutic modality for glioma via blocking cancer cell proliferation and inducing apoptosis by inhibiting NF-κB activity. Keywords:: embelin, glioma, proliferation, apoptosis, NF-κB